Determinant of Safety Riding Behavior of Motorcycle Riders - Febian Iskandar; Melda Yenni; Novi Berliana (Universitas Islam Negeri Alauddin Makassar, 2021)
Traffic accidents are still a global problem today. Indonesia is one of the countries that has a high level of traffic accidents. The number of traffic accidents in Jambi City in 2020 was 327 accidents, while traffic accidents in Paal Merah District were 53 accidents. To prevent accidents, drivers must apply safety riding in driving. The purpose of this study was to determine the factors associated with safety riding behavior on motorcyclists in Paal Merah sub-district. The study used a cross sectional design. The research was conducted in June 2021 on the Paal Merah sub-district highway located at the Paal Merah gas station in Jambi City. The research sample was motorcycle riders in Paal Merah District as many as 96 riders. The sampling technique was accidental sampling. The research instrument is a questionnaire. Data were analyzed using chi square test. A total of 53.1% of respondents have good safety riding behavior, 51.0% of respondents have good knowledge, 51.0% of respondents have good attitudes and 65.6% of respondents have good perceptions. Bivariate analysis showed that there was a relationship between knowledge (p=0.000), attitude (p=0.000) and perception (p=0.000) with safety riding behavior in Paal Merah District, Jambi City in 2021. It is expected that motorcycle riders always do safety riding when driving. even at close range and there is no inspection from the police.